Tailoring Mechanical Properties of Mg–Al–Zn–Sn–Mn Alloy by Multipass Equal Channel Angular Pressing. Issue 1 (21st January 2021) - Zha, Min; Wang, Chun-Xue; Jin, Zhong-Zheng; Jia, Hai-Long; Xu, Hong; Zhang, Ping-Yu; Huang, Yu; Ma, Ping-Kui; Wang, Hui-Yuan
Abstract : The relation between processing parameters (routes, passes) and mechanical behavior of equal channel angular pressing (ECAP) processed Mg alloys has been researched systematically by Hai‐Long Jia, and co‐workers in this article, number 2000790 . A low‐cost high‐strength‐ductility wrought Mg alloys has been made by combining fine DRXed grains, nano‐scale secondary phase particles and strong basal texture.